Research methods for counseling - "Wright, Robert J." (New Delhi, 2014)
Research Methods for Mental Health Professionals is a basic introductory research methods texts for counselors, psychologists, social workers, and other mental health professionals. The author will cover the basics of research including, the practitioner/researcher; qualitative methods, descriptive statistics, relationships, concordance and correlations, research design, dependent variables and samples, hypothesis testing, application of statistics to measurement, instrument development and survey research, action research, and evaluation. What makes this book unique is that it covers all the required aspects of CACREP reaccreditation standards including the practitioner as researcher, action research and evaluation. Other texts focus on qualitative and quantitative methods but neglect some of these other areas. The author intends to incorporate many case in point features, which depict a case example from a variety of disciplines. In addition, the text will contain cartoons and many tables and figures in every chapter.
Keywords: Counseling-Research-Methodology